Flux pinning and relaxation in FeSe0.5Te0.5 single crystals. (22nd January 2016) - Wu, Z F; Wang, Z H; Tao, J; Qiu, L; Yang, S G; Wen, H H
Abstract: A high-quality FeSe0.5 Te0.5 single crystal with T c ∼ 14.8 K was obtained by the self-flux method. We present the temperature dependence of resistivity at various fields and the magnetization hysteresis loops at various temperatures. The upper critical field H c2 ( T ) with a criterion of 90% ρ n follows H c2 ( T ) = H c2 (0)[1− T / T c ] n . A second peak (namely the fishtail effect) was observed in a large temperature region ranging from 6.5 K to 12 K. According to the theory of Dew-Hughes, we scaled the flux pinning force density for several fixed temperatures and found its maximum position around h = 0.33, here h is the reduced magnetic field. The dynamical relaxation rate Q of the vortices was measured and discussed.